2023
DOI: 10.1111/ans.18336
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of immediate facial nerve reanimation with nerve transfer for facial nerve neoplasm‐induced paralysis: a retrospective review

Abstract: Background: The purpose of this study was to evaluate the outcomes of our polyneural, zone-based reanimation approach for patients with neoplasm-induced facial paralysis. Methods: A retrospective review of consecutive patients who underwent facial reanimation surgery using multiple donor nerve transfers was undertaken. In each case, the selection of donor nerves was based on the availability of donor nerve and the viability of the motor endplate on the affected side. Sources of the neural inputs utilized inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…The facial nerve angle was defined as the angle between the inner margin of the facial acoustic nerve and the anterior surface of the brainstem at the point of nerve exit ( 8 ). Shein et al found that patients with smaller facial nerve angles had a higher incidence of hemifacial spasm ( 8 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The facial nerve angle was defined as the angle between the inner margin of the facial acoustic nerve and the anterior surface of the brainstem at the point of nerve exit ( 8 ). Shein et al found that patients with smaller facial nerve angles had a higher incidence of hemifacial spasm ( 8 ).…”
Section: Methodsmentioning
confidence: 99%
“…The facial nerve angle was defined as the angle between the inner margin of the facial acoustic nerve and the anterior surface of the brainstem at the point of nerve exit ( 8 ). Shein et al found that patients with smaller facial nerve angles had a higher incidence of hemifacial spasm ( 8 ). Based on this, we speculated whether there was a critical value for the facial nerve angle that correlated with the progression rate of HFS patients.…”
Section: Methodsmentioning
confidence: 99%